2023
DOI: 10.1021/jacs.3c09805
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Energy-Storage Density Together with Efficiency of above 90% via Local Structure Design

Huajie Luo,
Zheng Sun,
Ji Zhang
et al.

Abstract: Dielectric ceramic capacitors with high recoverable energy density (W rec ) and efficiency (η) are of great significance in advanced electronic devices. However, it remains a challenge to achieve high W rec and η parameters simultaneously. Herein, based on density functional theory calculations and local structure analysis, the feasibility of developing the aforementioned capacitors is demonstrated by considering Bi 0.25 Na 0.25 Ba 0.5 TiO 3 (BNT−50BT) as a matrix material with large local polarization and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To satisfy these requirements, a series of methods, represented by polymorphic nanodomain engineering in the BaTiO 3 –BiFeO 3 –SrTiO 3 ternary system, superparaelectric phase design in the SmO-doped BiFeO 3 –BaTiO 3 solid solution, and a high-entropy strategy in (K,Na)­NbO 3 ceramic and Bi-layered films, , has been developed to accomplish nanopolar instability and concomitant high-energy storage. Certainly, the local lattice strain between nanophases and the chemical pressure induced by chemical dopants or point defects play indispensable roles in the manipulation of local polar fluctuations. However, the intricate interactions and chemical flexibility hinder the decoupling of the pure lattice-strain effect. Recent studies have revealed the evolution of polar nanoregions in the established Pb­(Mg,Nb)­O 3 –PbTiO 3 relaxer under the modulation of various epitaxial strain states .…”
Section: Strain Engineering In Ferroelectric-based Applicationsmentioning
confidence: 99%
“…To satisfy these requirements, a series of methods, represented by polymorphic nanodomain engineering in the BaTiO 3 –BiFeO 3 –SrTiO 3 ternary system, superparaelectric phase design in the SmO-doped BiFeO 3 –BaTiO 3 solid solution, and a high-entropy strategy in (K,Na)­NbO 3 ceramic and Bi-layered films, , has been developed to accomplish nanopolar instability and concomitant high-energy storage. Certainly, the local lattice strain between nanophases and the chemical pressure induced by chemical dopants or point defects play indispensable roles in the manipulation of local polar fluctuations. However, the intricate interactions and chemical flexibility hinder the decoupling of the pure lattice-strain effect. Recent studies have revealed the evolution of polar nanoregions in the established Pb­(Mg,Nb)­O 3 –PbTiO 3 relaxer under the modulation of various epitaxial strain states .…”
Section: Strain Engineering In Ferroelectric-based Applicationsmentioning
confidence: 99%
“…Recently, researchers have made considerable investments in lead-free relaxor ferroelectric/antiferroelectric ceramics, which include NaNbO 3 (NN), 3,4 K 0.5 Na 0.5 NbO 3 (KNN), 5,6 BaTiO 3 (BT), 7,8 Bi 0.5 Na 0.5 TiO 3 (BNT), 9–11 and BiFeO 3 (BF) 12,13 ceramics. With a 3.4 eV broad band gap and significant polarization responses, NN-based ceramics are regarded as one of the potential choices among them.…”
Section: Introductionmentioning
confidence: 99%